PREDICTIVE ANALYTICS FOR ROUTE PLANNING, CARGO SCHEDULING, AND INTEGRATED PORT–SHIP LOGISTICS SYSTEMS - Korostin, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2025)
Artificial intelligence-based fleet management has become a central element in large-scale maritime operations. This trend is driven by the growing complexity of global supply chains and the need for more efficient utilization of available resources. The increasing volume of maritime cargo, the intensification of international trade, and the pursuit of reduced operational costs have created a strong demand for technologies capable of enabling continuous monitoring, rapid decision-making, and optimization across every stage of maritime transportation. The use of predictive analytics algorithms offers significant opportunities for accurate route planning, cargo flow control, delay minimization, and effective coordination between port infrastructure and vessel operations.